Comparison of non-alcoholic fatty liver disease (NAFLD) model using diet-induced NAFLD mice with genetically modified mice - Mohd Danial Mohd Efendy Goon,; Sharaniza Ab Rahim,; Normala Abd Latip,; Mardiana Abdul Aziz,; Norizal Mohd Noor,; Lew, Sook Weih; Musalmah Mazlan,; Siti Hamimah Sheikh Abdul Kadir, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Prevalence of non-alcoholic fatty liver disease (NAFLD) is increasing steadily every year affecting all population both Western and Asian countries. The current treatments available for NAFLD are non-conclusive warranting newer effective pharmacological agents. Newly formulated agents require prior testing using animal models. However, in developing countries, these models are often costly. The possibility of using more affordable animal model in local settings should be investigated. In this study, ten Institute of Cancer Research (ICR) and seven B6.Cg-LepOb/J leptin-knockout (JAX) male mice were recruited. Five ICR and all JAX mice were subjected to high-fat diet (60% kcal fat) and remaining ICR mice were given standard diet (SD) for six weeks. Body weight and food intake were measured weekly while abdominal circumference, random blood glucose and liver span were measured at the end of the HFD study. Livers collected were subjected to histology assessment. Compared to ICR group, JAX group presented with significantly higher body weight (58 ± 0.72, p<0.05), larger body weight changes (16.57 ± 0.81, p<0.05), more HFD intake (197.14 ± 0.812, p<0.05) and larger abdominal circumference (11.79 ± 0.34: p<0.05). Liver from JAX group appeared with general steatosis and presentation of high-grade panacinar steatosis, low number of lobular inflammations and minimal fibrosis. Liver of ICR mice showed Zone 3 steatosis with high number of lobular inflammations without fibrosis. The NAFLD characteristics presented in JAX group suggested that B6.Cg-LepOb/J mice developed characteristics of NAFLD resembling human while ICR is suitable NAFLD model resembling human population resilient towards NAFLD.